Effects of microRNAs in hypertension disease - Altıntaş, Nuray; Tonk, Onur; Sarıca Yılmaz, Özge (The European Research Journal, 2022)
Hypertension is a cardiovascular disease which is a very common hemodynamic syndrome, and it has different prevalence in different regions as it is common all over the world. In recent studies, it is known that microRNAs (miRNAs) play an important role in hypertension disease and that miRNA expressions are regulated by epigenetic mechanisms. There are also studies proving that microRNAs are new therapeutic targets for pulmonary arterial hypertension, and miRNAs can participate in the pathophysiology of hypertension in many ways and it can be used as a biomarker for hypertension disease. It is thought that miRNAs can be effective in the diagnosis and treatment of hypertension and further studies are needed. Recently, the relationship between miRNAs and hypoxia has also been focused on and has been taken into account in studies. In this review, we aimed to present the effects of miRNAs on hypertensive disease and current approaches. Finally, with gene targeting studies, we think that miRNAs, which can be biomarkers and molecular agents, will hold promise in preventing the progression of hypertension in the future, and we hope that they can create ideas for future studies.